Changes in countermovement vertical jump force-time metrics during a game in professional male basketball players - Cabarkapa, D.; Johnson, Q. R.; Cabarkapa, D. V.; Philipp, N. M.; Eserhaut, D. A.; Fry, A. C. (The Journal of Strength and Conditioning Research, 2024)
As technology within elite basketball advances and is more available to sporting organizations, novel approaches for assessing and addressing athletic performance during practice or competition are being continuously explored. The aim of this investigation was to examine changes in neuromuscular performance during live basketball play. Eight professional male basketball players volunteered to participate in this study. The testing procedures were conducted during a pre-tournament camp over a span of 2 days. During the first day, the athletes were familiarized with the testing procedures, and baseline measurements were obtained. Using a uni-axial force plate system sampling at 1,000 Hz, each athlete performed 3 countermovement vertical jumps (CVJ) without an arm swing before proceeding with their regular training activities. During the second day of the pre-tournament camp, the athletes repeated identical CVJ testing procedures before the start of the first quarter and post-first, second, third, and fourth quarter of a simulated 5-on-5 basketball game. Repeated-measures testing design was used to examine statistically significant differences in various force-time metrics of interest in comparison to the baseline levels (p < 0.05). Besides a trivial decrease in eccentric mean force, the findings of this study revealed no statistically significant changes in any force-time metrics of interest within both eccentric and concentric phases of the CVJ (i.e., mean and peak force and power, jump height, impulse, velocity, and contraction time). Thus, we can conclude that these variables were not sensitive to acute fatigue, suggesting that the neuromuscular performances of professional male basketball players tend to remain unchanged throughout a 5-on-5 simulated game.